Australian and New Zealand contribution to Plastic Surgery. Issue 7 (3rd March 2021) - Yousef, Justin; Morrison, Wayne
Abstract: Background: Plastic and Reconstructive Surgery (PRS) can trace its origins as far back as 3000 BC. Despite this, it remained a relatively rare and unestablished branch of surgery until the devastating injuries of the World Wars necessitated reconstruction. Returning wartime surgeons used the skills they had learned on the battlefield to continue PRS in Australia and New Zealand. This article examines the significant contributions of Australian and New Zealand surgeons to the founding of PRS as a global specialty and provides an account of the strenuous dedicated competition that led to the development of microsurgery and advances in reconstruction. Methods: A comprehensive review of medical, medical humanities, and history databases (PubMed; MEDLINE; Web of Knowledge; Anthropology; Encyclopaedia of ancient history) and non‐digital printed texts was conducted using multiple search terms and filters including Reconstruction; Plastic Surgery; Burns; Flaps; and Microsurgery). The search was restricted to publications that focused on the period between 1818 CE to current. Results: Significant contributions of surgeons from the Antipodes occurred during several periods including the Industrial era, World Wars, Post‐war and in the modern age. Conclusions: Stirred by their wartime experience, surgeons from Australia and New Zealand laid the foundations of the global success of Plastic Surgery in the modern age and helped establish it as a specialty in its own right. Abstract : Plastic and reconstructive surgery (PRS) can trace its origins as far back as 3000 BC. Despite this, it remained a relatively rare and unestablished branch of surgery until the devastating injuries of the World Wars necessitated reconstruction. Returning wartime surgeons used the skills they had learned on the battlefield to continue PRS in Australia and New Zealand. Stirred by their wartime experience, these veterans laid the foundations of the global success of Plastic Surgery in the modern age and helped establish it as a specialty in its own right. This article examines the significant contributions of Australian and New Zealand surgeons to the founding of PRS as a global specialty and provides an account of the strenuous dedicated competition that led to the development of microsurgery and advances in reconstruction.